Primary peritoneal low-grade serous carcinoma in a man: A case report and review of the literature - Jin Xu; Paul Weisman; Agnes Loeffler (Elsevier, 2017)
Primary peritoneal serous carcinoma (PPSC) almost always occurs in women, though rare cases have been reported in men. To date, only three cases of PPSC occurring in male patients have been published in the English literature. Here we describe the fourth case of primary peritoneal serous carcinoma in a male patient and the first showing morphologically and immunophenotypically confirmed low-grade serous histology. In addition to the classic morphologic features of low-grade serous carcinoma, the tumor cells show strong immunoreactivity for CK7, PAX8, WT-1 and ER, and very focal weak immunoreactivity for calretinin and CK5/6, supporting Müllerian serous differentiation. Mild to moderate cytological atypia and a wild-type staining pattern for p53 support a low-grade designation. Absence of a clinically detectable testicular or paratesticular primary tumor supports a primary peritoneal origin. The patient died shortly after his diagnosis; an autopsy was not performed.